THE HOUSING SUPPLY ELASTICITY AND ITS DETERMINANTS: EVIDENCE FROM CHINA - Ping Gao (Journal of Applied Economics in Developing Countries, 2014)
Using panel data for 35 cities in China from 1992 to 2009, this article estimates the flow model and the stock adjustment model based on the work by Malpezzi and Maclennan (2001). The flow model represents an implied housing supply elasticity varying from -0.004 to 0.819. In contrast, the stock adjustment model yields a slightly lower estimation ranging from -0.002 to 0.419. A further examination of the determinants of housing supply elasticity suggests that housing supply is not only significantly influenced by housing prices, but also by land-use regulations as well as the lagged housing stock.Keywords: Housing supply elasticity, housing stock, land regulations